(untitled) (Eurasian Research Bulletin, 2024)
Business risk management, which ensures the minimization of their negative impact and the impact on increasing the competitiveness of business structures due to the developed tools that ensure the integration of new information technologies into the business management system. Currently, in practice in modern companies, rational risk management is not widespread, but in recent years this area has been steadily developing. Not all large companies direct their efforts to identify and minimize their business risks, most consider insurance to be the only way to fight.